Coadministration of fluconazole to boost subtherapeutic sirolimus concentrations: a case report - Scherkl, Camilo; Meid, Andreas; Cuntz, Sven Enrico; Claßen, Laura; Weiß, Johanna; Czock, David; Haefeli, Walter E. (Pharmacology research & perspectives, 2024)
Individual sirolimus whole blood concentrations are highly variable, critically influenced by the concomitant use of cytochrome P450 (CYP) 3A inducers or inhibitors, and also modulated by food. Therapeutic drug monitoring is therefore recommended, especially at treatment start or in circumstances that can influence sirolimus exposure. In this case report, we highlight the challenge of achieving therapeutic sirolimus concentrations and present pragmatic solutions with regimen adaptions, pharmacokinetic enhancement (use of a drug-drug interaction), concentration monitoring, and subsequent modeling of population pharmacokinetics to support treatment decisions. In a 69-year-old female patient with allogeneic hematopoietic stem cell transplantation, sirolimus concentrations were stable until she developed cerebral toxoplasmosis with tonic-clonic seizures. During treatment of this acute infection, sirolimus concentrations dropped to subtherapeutic levels and remained largely unaffected by dose increases. [Correction added on 4 May 2024, after first online publication: The word “tacrolimus concentrations” has been changed to “sirolimus concentrations” in the preceding sentence.] Only the simultaneous administration of the CYP3A4 inhibitor fluconazole and a shortening of the sirolimus dosing intervals to a (non-approved) twice-daily administration led to successful control of the concentrations, which ultimately even made a dose reduction possible. This intervention resulted in an increase of sirolimus mean trough concentration to 5.85 ng/mL, i.e., into the desired target range. Additionally, a higher ratio of sirolimus trough levels/daily dose from 26.9 to 109 ng/mL/mg/kg/day was achieved with the initiation of fluconazole. Thus, this case report describes the use of clinical pharmacological concepts and pharmacokinetic modeling to optimize treatment strategies in an individual patient. This strategy could be generalized to other CYP inhibitors and other treatment regimens.
Online veröffentlicht: 18. April 2024
Gesehen am 02.07.2024